Commuting Behavior in the City Center of Vientiane Capital, Lao PDR: https://doi.org/10.69692/SUJMRD0901108 - Vongpraseuth, Thanousorn; Daravong, Sinthavone; Outhenthapanya, Dasack (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This study aims to clarify issues and directions for traffic problem solutions. Commuting behaviors and traffic flows both inbound and outbound in Vientiane Capital have been surveyed and conducted. Cross-sectional OD and household data are also collected. The econometric model has been processed in the analysis stage in order to understand the modal splits and trip behaviors. Commuting flows and modal split indicators would present the trip's purposes and directions. Regarding the analysis process, two crucial motorized transport modes have been illustrated: private motorbikes and cars for their daily trips. The high concentration of workplaces and activities would probably be in the city center and 5km from the city center areas by private transport modes. The key challenge of transport planning has been revealed as poor public transport modes. In order to mitigate the flow of traffic congestion in Vientiane Capital would be the providing and promoting of diverse transport modes both management and regulatory approaches. The investment in public facilities would help support the reality of solving congestion problems in the capital city of Laos.